Application of burnt clay bricks (BCBs) as a building material for housing projects in Ghana - Amos Ansah; Humphrey Danso (Cogent Engineering)
The use of locally available and abundant building materials facilitates the availability and affordability of housing. One of the important locally available building materials in Ghana is burnt clay bricks. The purpose of this study is to assess the application of burnt clay bricks (BCBs) as a building material for housing projects in Ghana. The study adopted a descriptive survey research design which collected data from 90 architects and occupants of burnt clay brick buildings. It was found that BCBs can be applied for pavements, walls of any size, arches and cornices, partition walls, exterior and interior walls, and applied in the construction of brick retaining walls. It was further revealed that perceived financial cost, risks of BCBs, low demand for BCBs, inadequate BCBs on the market, and low interest in the use of BCBs affect the application of BCBs as a building material. It was also found that lack of commitment to the use of BCBs, lack of awareness by developers, inadequate knowledge of developers, and the inability of BCBs to satisfy the needs of modern building forms and functions affect the application of BCBs as a building material. The study recommends that building clients and professionals consider the application of BCBs as a building material for construction projects.